Relaksasi Perizinan Lingkungan dalam Undang-Undang Nomor 11 Tahun 2020 tentang Cipta Kerja: Dampaknya terhadap Kelestarian Lingkungan dan Bisnis - Agnes Ruth Febianti (CV Rewang Rencang, 2022)
After the Constitutional Court of Indonesia declared it unconstitutional conditionally, the Law on Job Creation was declared valid within 2 years of the revision. Based on the enactment of the Law on Job Creation, the regulation in Law on the environment is changed in Law on Job Creation which previously drew criticism and is declared valid. There are criticisms of it regarding the environment in the Law on Job Creation. First, regarding Business Licences that abolish Environmental Permits, and the regulations regarding the issuance of AMDAL which is only a requirement for high-risk business activities. These policies are considered only concerned with the business sector without considering sustainable environmental preservation as regulated in the Law on Environmental Protection and Management.